Role of Corporate Social Responsibility in Environment Sustainability: The Indian Perspective: Exploring the relationship between CSR and sustainability in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Corporate Social Responsibility and Sustainable Development are popular terms in today‟sscenario. CSR and sustainability are as important for society and environment as profit earning forbusiness. CSR policies and sustainability practices are correlated with each other. Sustainability practicesmeans conducting business activities in a way that increase the stakeholders‟ earnings and minimizeenvironmental harm and contributing for social development activities. Through the sustainabilityinitiatives, companies can increase customer satisfactionand profits without harming environment.In fact, CSR activities and Sustainable Development are closely related with each other, follow all ethicalpolicies to perform their duties and conduct business activities in a sustainable manner. CSR is not onlya humanitarian activity but also a tactical initiative that is integrated with business activities. The IndianCompanies Act 2013, section 135(VII) indicatesthat there is a close relationship between CSR andsustainability. ISO 26000 guidelines also explains that the goal of CSR is to contribute in socialdevelopment, environmental protection and natural resources preservation . ISO 26000 describesCorporate Social Responsibility is a social and ethical obligations of the business organization for theeffects of its operations on environment through sheer and transparent behavior that contribute forsustainability, including health and welfare of society. This definition of CSR correlates CSR with thesociety and environmental components of sustainable development. CSR is a culture and unwrittencontract with the environment and society and this invisible culture can shape shinning futures for nextgenerations. Organizations all over the world had realized the importance of CSR and sustainability.Corporations all over the world are fighting for a new task, that is to satisfy the needs of presentgenerations without depleting natural resources for future generations to satisfy their own needs.Companies are being asked to implement all fundamentals in such a way in which they operate theirbusiness activit ies, CSR is also a prominent feature of the society. The main objective of this researchpaper was (1) To understand the efficiency of CSR in Indian and International perspective. (2) Toappraise various aspects related to CSR and sustainability. (3) To determine the interrelationship betweenCSR and Sustainability. To determine the various policies adopted by business organizations andproblems facedby organizations in applying these policies in India. (4) To provide remedial measures tosolve the problems faced in application of CSR policies. The nature of present paper is descriptive andanalytical and descriptive method isused for analysis of this paper.